Pengolahan Limbah Cair Industri Tahu Menggunakan Teknologi Ultrafiltrasi Dengan Sistem Monitoring Berbasis Internet of Things - N. H., Harmiwati; Yahya, Agung Kurnia; Luthfi, Muhammad Zulfikar; Nurmalasari, Enny; Permadani, Resi Levi; Aini, Apsari Puspita; Rahayu, Puji (Journal of Industrial Community Empowerment, 2024)
Waste from the tofu industry is a byproduct of the tofu production process that can have negative environmental impacts if not managed properly. CV. Dapur Tahu still discharges liquid waste directly into the river, posing a potential threat of river water pollution. Although a new reservoir and waste disposal channel are under construction, there is currently no effective waste treatment facility in place. To address this issue, a tofu wastewater treatment facility utilizing filtration technology is proposed due to its simplicity of operation, durability, and high efficiency in removing organic contaminants. The technology comprises a multi-stage filtration process involving sand filters (pumice, zeolite, and activated charcoal) combined with ultrafiltration membrane technology, complemented by a monitoring system consisting of TDS, pH, and temperature sensors. The multi-stage filtration process is capable of reducing TDS levels to 160 ppm, resulting in visibly clearer wastewater compared to the initial turbid white condition. The installation of IoT-based monitoring devices in the wastewater treatment process significantly aids in real-time water quality monitoring, accessible via mobile phone screens.